Transport properties of saturated sucrose and maltitol solutions as affected by temperature - Martins, Maria Julia Neves [UNESP]; Augusto, Pedro Esteves Duarte; Telis-Romero, Javier [UNESP]; Polachini, Tiago Carregari [UNESP] (Elsevier, 2021)
Saturated sugar solutions have been used to enhance mass transfer in osmotic dehydrations processes and as ingredients in food and pharmaceutical industries. Although sucrose is a traditional and versatile solute, consumers demand the use of natural sweeteners as maltitol to formulate foods with reduced calorie. However, the thermophysical properties of those saturated solutions are rarely reported in the literature. Therefore, this work determined transport properties (solubility, density, viscosity, specific heat, thermal conductivity and thermal diffusivity) of saturated solutions of sucrose and maltitol in a wide range of temperatures. Empirical and theoretical models were fitted to the experimental data. Solubility of maltitol was more strongly influenced by temperature than sucrose. For both solutions, density and thermal diffusivity showed increasing values with increasing temperature while specific heat and thermal conductivity showed decreasing values at the same conditions. Although viscosity of saturated sucrose solutions decreased with increasing temperature, increasing viscosities were observed for maltitol solutions at the same temperatures. Proposed models showed good fitting accuracy (R2 ≥ 0.83673; MRE ≤ 13.07%), creating an important and accurate database for saturated solutions of sucrose and maltitol for further applications in different processes.
Keywords: Mathematical modeling; Natural sweeteners; Polyol solutions; Sugar solutions; Thermophysical properties